Different patients, different outcomes: A case‐control study of spontaneous coronary artery dissection versus acute coronary syndrome. (20th September 2017) - Adams, Heath; Paratz, Elizabeth; Somaratne, Jithendra; Layland, Jamie; Burns, Andrew; Palmer, Sonny; MacIsaac, Andrew; Whitbourn, Robert
Abstract : Introduction: There is progressive interest worldwide in spontaneous coronary artery dissection (SCAD). To identify a SCAD cohort and compare risk factors, presentation, and management outcomes compared to acute coronary syndrome (ACS) matched controls. Methods: Retrospective analysis was performed from 2000 to 2015. Clinical data included a neuropsychiatric history, with management and clinical outcomes assessed at 12 months. Patients were matched on a 1:3 case‐control basis according to type of ACS. Twenty‐two SCAD patients were matched to 66 controls by ACS type (ST‐elevation myocardial infarction 45%, Non‐ST‐elevation myocardial infarction 41%, unstable angina 14%). Results: The SCAD group were more likely female (77.3% vs 19.7%, P < 0.0001), of younger age (48.7 ± 10.7 years vs 61.3 ± 10.6 years, P < 0.0001) with no cases of diabetes (0% vs 33.3%, P = 0.002), compared to controls. SCAD patients had a high prevalence of anxiety, depression or previous neuropsychiatric history (52.4% SCAD vs 1.5% ACS, P < 0.0001). A conservative revascularization strategy with stenting was performed in a minority of SCAD patients (13.6% SCAD vs 83.3% ACS, P < 0.0001), with no significant difference in cumulative major adverse cardiac or cerebrovascular events (MACCE) of death, stroke, re‐admission, or repeat angiography rates between both groups (13.6% SCAD vs 27.3% ACS P = NS). Conclusion: SCAD affects young females with a paucity of cardiovascular risk factors. The major risk factor for SCAD was a history of anxiety, depression, or neuropsychiatric illness. A conservative approach to SCAD revascularization led to similar MACCE when compared to ACS controls undergoing guideline revascularization at 12 months.